Existential prayer in the light of Classical Functionalism - Alves Costa, Lucas (Revista (Entre Parênteses), 2024)
The existential sentence, with the verbs ter, haver and existir, has specific morphosyntactic, semantic and discursive features in the Portuguese language. The objective is to carry out bibliographical research on some concepts of Classical Functionalism, such as valence, transitivity, detransitivity, impersonality, definiteness and indefiniteness, to analyze this prayer. To this end, it is based on the works of Dik (1989), Givón (1979, 1990), Halliday (1973), Hopper and Thompson (1980), Hopper (1987) and others. Language-in-use data was derived from a sample of the Portuguese NOW Corpus. It was found that the concepts of Classical Functionalism are efficient for the analysis of the existential sentence, as they mainly provide a continuous vision of the linguistic phenomenon and an integral approach to the grammatical components.